«Літературний ярмарок» як об'єкт пародіювання (на матеріалі пародій Едварда Стріхи) - Кисіль, В.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2007)
Рассмотрено художественному оформлению Эдвардом Стрихой 138-го номера журнала «Литэратурный ярмарок». При оформлении журнала Стриха использует пародийные приемы. Ему удается объединить с помощью собственных пародий произведения писателей, которые печатались в номере журнала в единое целое. This article is dedicated to the taking part of K. Bureviy in the staging of the 138-th number of “Literature fair”. K. Bureviy paradied “Literature fair”and authors that were published in this journal. The text of this article also included opinions of critics on the staging of “Literature fair” by K. Bureviy.
Keywords: «Літературний ярмарок»; Стріха; пародія